Disaster Citizenship: Survivors, Solidarity, and Power in the Progressive Era - Remes, Jacob A. C. (The working class in American history, 2015)
A century ago, governments buoyed by Progressive Era–beliefs began to assume greater responsibility for protecting and rescuing citizens. Yet the aftermath of two disasters in the United States-Canada borderlands--the Salem Fire of 1914 and the Halifax Explosion of 1917--saw working class survivors instead turn to friends, neighbors, coworkers, and family members for succor and aid. Both official and unofficial responses, meanwhile, showed how the United States and Canada were linked by experts, workers, and money. In Disaster Citizenship , Jacob A. C. Remes draws on histories of the Salem and Halifax events to explore the institutions--both formal and informal--that ordinary people relied upon in times of crisis. He explores patterns and traditions of self-help, informal order, and solidarity and details how people adapted these traditions when necessary. Yet, as he shows, these methods--though often quick and effective--remained illegible to reformers. Indeed, soldiers, social workers, and reformers wielding extraordinary emergency powers challenged these grassroots practices to impose progressive "solutions" on what they wrongly imagined to be a fractured social landscape. Innovative and engaging, Disaster Citizenship excavates the forgotten networks of solidarity and obligation in an earlier time while simultaneously suggesting new frameworks in the emerging field of critical disaster studies.